Effects of discovery learning and student assessment on academic success - Suphi, Nilgün; Yaratan, Hüseyin (Sakarya University editor@tojet.net, 2016)
In this study the effect of Discovery Learning and course evaluation based on Bloom’s Taxonomy on the academic success of undergraduate students in Northern Cyprus was investigated. One demographic questionnaire was distributed to 829 students and two questionnaires were distributed to these students’ instructors in order to collect information on the extent they used the Discovery Learning method as well as ascertaining the complexity level of learning intended to be achieved based on the criteria used for course evaluation (e.g. homework, project, and examination). Fourteen instructors of a total of nine courses and 34 classes participated in this study. The results indicated the higher the use of Discovery Learning during the course the lower the course grades were found to be. Also the higher the cognitive level of learning (e.g. analysis, synthesis and evaluation used by the instructor for the course, the lower the course grade was achieved by the students. © The Turkish Online Journal of Educational Technology.
Keywords: Academic success; Cognitive level of learning; Discovery learning